CORAL REEF REHABILITATION IN THE SALEH BAY WEST NUSA TENGGARA - Sri Turni Hartati; Didik Wahju Hendro Tjahjo; Awwaluddin Awwaluddin (Indonesian Fisheries Research Journal, 2011)
The covering area damages noted up to the year of 2000 for the Western Saleh Bay's coral reefs were ranged from 48.24-66.37%.